Froebel dan Kognitif Anak Usia Dini: Telaah Teoretis tentang Peran Bermain Terstruktur dalam Meningkatkan Kemampuan Berpikir - Nelia Guswanti; Panggung Sutapa (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to examine the relevance of Friedrich Froebel's play theory to the cognitive development of early childhood and to formulate a conceptual model for the application of structured play in early childhood education. This study uses a literature review approach by analyzing scientific articles, books, and research findings from 2020–2025. The results of the study indicate that Froebel's concept of gifts and occupations functions as a concrete manipulative medium that can stimulate children's logical thinking skills, creativity, working memory, and representational abilities. Structured play allows children to explore basic mathematical concepts, patterns, spatial relationships, and problem-solving processes through direct experience. This article offers the "Froebel Structured Play for Cognitive Strengthening (BTF-PK)" model as an implementation framework in modern early childhood education. This study provides theoretical benefits in enriching the literature related to early childhood education and practical benefits in the form of recommendations for the application of structured play for early childhood teachers